Structure-activity studies of dodecatungstophosphoric acid impregnated bentonite clay catalyst in hydroxyalkylation of p-cresol - Garade, Ajit C.; Kshirsagar, V. S.; Jha, Ajay; Rode, C. V. (Catalysis Communications, 2010)
Bentonite clay impregnated with dodecatungstophosphoric acid (20% DTP/BNT) showed an excellent activity, selectivity and stability [95% product yield with 94% selectivity to 2, 2'-methylenebis (4-methylphenol), DAM] for the hydroxyalkylation of p-cresol with formaldehyde at 353 K and for a mole ratio of 5. Ammonia-TPD results showed that an increase in total concentration of acid sites from 4.9 of parent bentonite to 11.6 micromoles per surface area NH(3) (mu molS(-1) NH(3)) of 20% DTP/BNT was due to a strong interaction of protons of bulk DTP with surface hydroxyl groups of BNT as evidenced by (31)P NMR studies. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: (31)P CPMAS NMR; Bentonite; Hydroxyalkylation; p-Cresol; surface modification

Na-montmorillonite to Fe(II)-Mt using ferrous citrate/ascorbate obtained by dissolving iron powder - S. Chikkamath; J. Manjanna; N. Momin; B.G. Hegde; G.P. Nayaka; Aishwarya S. Kar; B.S. Tomar (Applied Clay Science, 2022)
Bentonite containing montmorillonite (Mt) as the major clay mineral is the potential buffer material of engineered barrier system in the deep geological repository for high-level waste management. The corrosion products of canister/or overpack material (carbon steel) may alter the basic characteristics of bentonite through Fe/clay interaction and formation of FeMt to certain extent. A convenient method is required for quantitative preparation of Fe(II)-Mt because the only few direct methods reported have some limitations. For this, weak ferrous complexes having good solubility to facilitate the cation-exchange with bentonite is essential. Therefore, Fe(II)-citrate, Fe(II)-ascorbate and Fe(II)-citrate/ascorbate were obtained here by dissolving the iron powder (Fe0) in citric acid (CA), ascorbic acid (AA) and their equimolar mixtures from 25 mM to 300 mM at 70 °C under N2 atmosphere. The redox potential was measured to monitor the dissolution of Fe0 in these mild organic acids. Higher dissolution of Fe0 occurred in CA + AA mixture. The dissolved iron in the form of ferrous complex was reasonably stable in inert atmosphere, Fe2+/Fetotal ≈ 1. The parent clay mineral (bentonite, NaMt) was treated with Fe(II) − cit/asc to form Fe(II) − Mt. through cation exchange process. The CEC and ferrous to ferric ratio of the Fe(II)-Mt was close to the stoichiometric amount. The XRF, XRD, ac impedance, FT-IR, TGA/DSC, XPS and FE-SEM are used for further characterization. In-situ complexation reaction of interlayer Fe2+ ions in Fe(II)-Mt with o-phenanthroline was also observed.
Keywords: Ascorbic acid; Bentonite; Citric acid; Cr(VI) reduction; Fe(II)-montmorillonite; Iron dissolution

Hydrogenation of levulinic acid to gamma-valerolactone over nickel supported organoclay catalyst - Kamble, Paresh A.; Vinod, C. P.; Rathod, Virendra K.; Kantam, Mannepalli Lakshmi (Catalysis Today, 2023)
In this work, a series of Ni/Organoclay catalysts with different Nickel loadings were prepared by the wetimpregnation method for the catalytic hydrogenation of levulinic acid (LA) to gamma-valerolactone (GVL). Reaction parameters such as reaction temperature, pressure, solvent effect, and wt% of catalyst were optimized to get excellent conversion of levulinic acid selectively to gamma-valerolactone. Ni/Organoclay with 30% Nickel loading exhibited 100% conversion of LA with 100% selectivity towards GVL at 140 degrees C and 3.0 MPa H2 pressure using 1,4-dioxane as a solvent in 5 h. Different bulk and surface characterization techniques such as XRD, BET, FE-SEM, HR-TEM, XPS, XRF, NH3-TPD, and H2-Chemisorption were used to characterize the Ni/Organoclay catalyst. BET and NH3-TPD analysis showed that the pre-treatment of bentonite with surfactant (CTAB) improved the pore volume, surface area, and acidity of Organoclay which assisted in improving the conversion and selectivity of LA and GVL respectively.
Keywords: ?-Valerolactone (GVL); Bentonite; Hydrogenation; Levulinic acid (LA); Nickel; organoclay